Incidence, risk factors and outcomes of traumatic head injury among trauma patients visited at the Yanet Trauma and Surgery Specialized Centre, Sidama region, Hawassa, Ethiopia: cohort study - Abebe, Tadelech; Alemu, Tsegaye; Sorato, Mende Mensa (Frontiers in Neurology, 2024)
Introduction Traumatic brain injuries are a major public health concern that contributes to youth morbidity and mortality in developing nations, including Ethiopia. Despite of this, little is known about head injury in the study area. The goal of the study was to identify the incidence, risk factors and outcomes for traumatic head injury among trauma patients who visited at the Yanet Trauma and Surgery Specialized Centre. Methods This was a 5 year an institutional-based retrospective cohort study conducted among 1,029 patients who experienced trauma and admitted at the Yanet Trauma and Surgical Specialized Centre. The research was carried out between September 01/2023 to October 15/2023. The study units were selected by using simple random sampling techniques through computer-generated random numbers. The data were collected via a checklist designed on the Kobo toolbox with a smart smartphone. The collected data were exported to a statistical package for Social Science version 27. Then, descriptive statistical analysis was conducted to determine the mean, standard deviation, and median. Bivariate and multivariate logistic regression was subsequently conducted to determine the associations between head injury and the independent variables. Result A total of 1,029 injured patients were followed for 2,302 person-days. Over all, incidence density rate of 14.03/100 person-days (323, 31.4%) [95% CI: 29.5–34%]. The third year of follow-up showed the greatest incidence compared to other years. The most common type of head injury observed during following up were brain contusion (38.1%), followed by epidural hematoma (33.1%), skull fracture (15.8%), and intracerebral hematoma (13.0%). In multivariate logistic model, rural residence [AOR = 1.6; 95% CI: 1.18–2.16], mechanism of injury namely road traffic accident [AOR = 5.5; 95% CI: 2.27–13.34], assault [AOR = 3.4; 95% CI: 1.35–8.37] and comorbidity of chronic disease [AOR = 2.2; 95% CI: 1.13–4.18] were the risk factors significantly associated with head injury. Discussions The incidence density rate of 14.03/100 person-days. As the result, more has to be done by health professionals, traffic police officers and local government raise awareness and enforce the implementation of driving rules and regulations.